Near‐Infrared Colorimetric and Ratiometric Fluorescence Sensor for Fluoride Ions. Issue 26 (13th July 2022) - Dai, Hui; Yang, Jinglian; Ye, Zijian; Liu, Cong; Xu, Bingjia; Shi, Guang; Su, Shichen; Zhang, Yujian; Chi, Zhenguo
Abstract: Two novel benzothiadiazole derivatives were prepared. Clear color changes from orange‐red to blue (DPCN) and pink to green (DPTPE) were observed after the addition of fluoride ions (F − ). DPCN and DPTPE displayed ratiometric fluorescence changes in the presence of F − . 1 H‐NMR titration and DFT calculations confirmed deprotonation in the presence of F − . Compared with DPTPE, the hydrogen proton of the imine group in DPCN had higher activity due to the influence of the strong electron‐withdrawing cyano group, such that it was more easily deprotonated and the detection limit for F − was much lower. This work provided guidance for the further design and preparation benzothiadiazole based colorimetric and ratiometric fluorescence sensor for F − . Abstract : Two novel benzothiadiazole (BTD) derivatives with two fluorescence peaks of locally excited (LE) and charge transfer (CT) process are prepared. They can detect F − by means of deprotonation, showing colorimetric and ratiometric fluorescence. Compared with DPTPE molecule, the proton of imine group in DPCN has higher activity due to the influence of the strong electron‐withdrawing cyano group, so the detection limit for F − is much lower. This work provides guidance for dual‐emission fluoride ion colorimetric and ratiometric fluorescence sensors.